Thermal - Static Analysis of the Brake Disc in SolidWorks - Kostialikova, Daniela; Janekova, Mariana; Dubcova, Petra; Hulc, Marek (Manufacturing Technology Journal, 2024)
The work deals with the creation of 3D model of a disc brake of a personal vehicle, followed by a simula-tion of thermal and strengh analysis during car braking in the SolidWorks program. The disc brake is made of a gray cast iron, the most common material for this application. Cast iron discs offer excellent performance, making them suitable for various types of vehicles. The deformation of a brake disc was analyzed by using the program SolidWorks, where the first a simulation of the thermal load was per-formed, the aim of which was to determinate the temperature distribution on the brake disc and display the temperature rise during braking. In the next part, the simulation of strength deformation was carried out, and thus determination of the ther-mal load effect of the brake pads on the brake disc.
Keywords: Disc brake; Thermal analysis; Static analysis; Drum brakes; SolidWorks